Analisis Struktur Gedung Sport Center dan Parkir Sumatera Selatan Menggunakan Sistem Rangka Pemikul Momen Khusus (SRPMK) - M. Habib Diva; Syahril Alzahri; M Firdaus (Civil Engineering Department, Faculty of Engineering, Universitas Swadaya Gunung Jati, 2026)
This study evaluates the structural performance of a four-story sports center and parking building in South Sumatra designed using a Special Moment Frame System (SMFS). The building has a total height of 17.55 m, with reinforced concrete structures on floors 1–3 and a steel H-beam system on the fourth floor. The materials used are 30 MPa concrete and 420 MPa reinforcing steel. Structural analysis was performed using STAAD.Pro V8i with the response spectrum method in accordance with SNI 1726:2019, considering site class SE and seismic parameters SDS = 0.434 g and SD1 = 0.363 g. The applied load combinations include gravity and seismic loads in both principal directions. The results show that the maximum interstory drift in X and Y directions is well below the allowable limits, and the structure satisfies the Strong Column–Weak Beam requirement (ΣMnc ≥ 1.2 ΣMnb), ensuring ductile seismic behavior. Design comparison indicates several construction-driven modifications, including changes in column cross-sections and the use of steel framing at the fourth floor, which were verified to remain compatible with the overall structural system. Overall, the structure demonstrates adequate seismic performance and code compliance.